DIAGNOSIS CRITERIA OF MOLAR INCISOR HYPOMINERALIZATION SYNDROME: A CASE REPORT - Camelia Mona Brînză; Vasilica Toma; Carmen Savin; Ana Sîrghe; Petra Surlin (Romanian Society of Oral Rehabilitation, 2020)
The term molar-incisor hypomineralization describes an uncommon pathological entity characterized by the hypomineralization of permanent first molars and commonly affecting permanent incisors. In this paper, we describe a case of a 12 years old male patient attended with severe dental sensibility, masticatory and phonetic difficulties. Clinical examination revealed extended atypical restorations on permanent first molars, associated with opacities at the border of the restorations, enamel breakdown and opaque stains affecting permanent incisors. MIH diagnosis for this case is justified not only by the visual aspect of the lesions, but also by dental affection pattern.